Childhood Posterior Fossa Tumours: Experience from a Tertiary Center in Nepal - Thapa, Bikas; Pradhanang, Amit Bahadur; Sedain, Gopal; Shilpakar, Sushil Krishna; Sharma, Mohan Raj (Journal of Karnali Academy of Health Sciences, 2024)
Background: Brain tumour is a common problem in paediatric age group and posterior fossa is the commonest location. Treatment of these tumours is difficult due to a confined space and potential involvement of brainstem. The aim of this study is to analyse the clinical features, radiological findings, pathological diagnosis, surgical management, postoperative complications and outcome in 3 months in paediatric patients with posterior fossa tumours. Method: Retrospective chart review of 24 patients treated in the Department of Neurosurgery, TUTH, between 2019 April – 2023 April was done. The variables included were age, sex, clinical features, radiological findings, histopathological diagnosis, management and postoperative complications. Results: Twenty-four patients (30%) out of 80 childhood tumors were located in posterior fossa. The most common presenting symptoms was headache in 83.3% and vomiting in 75%. The most common location of tumour was the fourth ventricle in 66.7% while most common tumour histology was Type IV medulloblastoma in 45%. The commonest mode of treatment in 90% of cases was Ventriculoperitoneal (VP) shunting followed by surgical excision of tumour. Conclusion: Posterior fossa tumours are common tumour occurring in children. Majority of the patients presented with features of raised intracranial pressure and gait ataxia. Fourth ventricle and cerebellar vermis are the most common location. Most common histology types are medulloblastoma followed by pilocytic astrocytoma and ependymoma. Management involves addressing acute hydrocephalus followed by definitive surgery.